Improved genetically-encoded, FlincG-type fluorescent biosensors for neural cGMP imaging - Bhargava, Yogesh; Hampden-Smith, Kathryn; Chachlaki, Konstantina; Wood, Katherine; Vernon, Jeffrey; Allerston, Charles K.; Batchelor, Andrew M.; Garthwaite, John (Frontiers in Molecular Neuroscience, 2013)
Genetically-encoded biosensors are powerful tools for understanding cellular signal transduction mechanisms. In aiming to investigate cGMP signalling in neurones using the EGFP-based fluorescent biosensor, FlincG (fluorescent indicator for cGMP), we encountered weak or non-existent fluorescence after attempted transfection with plasmid DNA, even in HEK293T cells. Adenoviral infection of HEK293T cells with FlincG, however, had previously proved successful. Both constructs were found to harbour a mutation in the EGFP domain and had a tail of 17 amino acids at the C-terminus tail that differed from the published sequence. These discrepancies were systematically examined, together with mutations found beneficial for the related GCaMP family of Ca2+ biosensors, in a HEK293T cell line stably expressing both nitric oxide (NO)-activated guanylyl cyclase and phosphodiesterase-5. Restoring the mutated amino acid improved basal fluorescence whereas additional restoration of the correct C-terminal tail resulted in poor cGMP sensing as assessed by superfusion of either 8-bromo-cGMP or NO. Ultimately, two improved FlincGs were identified: one (FlincG2) had the divergent tail and gave moderate basal fluorescence and cGMP response amplitude and the other (FlincG3) had the correct tail, a GCaMP-like mutation in the EGFP region and an N-terminal tag, and was superior in both respects. All variants tested were strongly influenced by pH over the physiological range, in common with other EGFP-based biosensors. Purified FlincG3 protein exhibited a lower cGMP affinity (0.89 µM) than reported for the original FlincG (0.17 µM) but retained rapid kinetics and a 230-fold selectivity over cAMP. Successful expression of FlincG2 or FlincG3 in differentiated N1E-115 neuroblastoma cells and in primary cultures of hippocampal and dorsal root ganglion cells commends them for real-time imaging of cGMP dynamics in neural (and other) cells, and in their subcellular specializations.